Design and Evaluation of a Web-Based Geographic Information System for PPDB Promotion Zoning Based on Student-Origin Distributions - Riko Muhammad Suri; Ahmad Risman; Sidik Praptomo (Journal of Electrical Engineering and Computer (JEECOM), 2025)
Advances in information technology have accelerated the digitalization of educational services, including Indonesia’s student admission process (PPDB). This study designs and evaluates a web-based Geographic Information System (GIS) to map student-origin distributions and construct promotion zones that guide PPDB outreach strategies. The system was built with CodeIgniter and Leaflet for interactive mapping, while applicant addresses/school origins were processed via geocoding. Outputs include point maps, density heatmaps, administrative-area aggregation (urban village/sub-district), and simple distance buffers (e.g., 1–3 km) to derive rule-based priority promotion zones (thresholds on density and proximity to the school). Evaluation comprised functional testing (black box) and user assessments using questionnaires (Likert/SUS). Results indicate that the system expedites registration, reduces the risk of data loss, simplifies data summarization, and provides promotion-zoning maps that help committees target outreach more effectively. The contributions are: (1) a PPDB web-GIS model that combines origin mapping with rule-based promotion zoning, (2) a replicable operational workflow, and (3) recommendations for future work, including advanced analytics dashboards and automated notifications